Ambient condition bias stress stability of vanadium (IV) oxide phthalocyanine based p-channel organic field-effect transistors. (7th December 2017) - Obaidulla, Sk Md; Singh, Subhash; Mohapatra, Y N; Giri, P K
Abstract: High bias-stress stability and low threshold voltage ( V th ) shift under ambient conditions are highly desirable for practical applications of organic field-effect transistors (OFETs). We demonstrate here a 20-fold enhancement in the bias-stress stability for hexamethyledisilazane (HMDS) treated vanadium (IV) oxide phthalocyanine (VOPc) based OFETs as compared to the bare VOPc case under ambient conditions. VOPc based OFETs were fabricated on bare (non treated) SiO2 and a HMDS monolayer passivated SiO2 layer, with an operating voltage of 40 V. The devices with top contact gold (Au) electrodes exhibit excellent p-channel behavior with a moderate hole mobility for the HMDS-treated device. It is demonstrated that the time dependent ON-current decay and V th shift can be effectively controlled by using self-assembled monolayers of HMDS on the VOPc layer. For the HMDS-treated case, the bias stress stability study shows the stretched exponential decay of drain current by only ~15% during the long-term operation with constant bias voltage under ambient conditions, while it shows a large decay of  >70% for the nontreated devices operated for 1000 s. The corresponding characteric decay time constant ( τ ) is 10 4 s for the HMDS treated case, while that of the the non-treated SiO2 case is only ~480 s under ambient conditions. The inferior performance of the device with bare SiO2 is traced to the charge trapping at the voids in the inter-grain region of the films, while it is almost negligible for the HMDS-treated case, as confirmed from the AFM and XRD analyses. It is believed that HMDS treatment provides an excellent interface with a low density of traps and passivates the dangling bonds, which improve the charge transport characteristics. Also, the surface morphology of the VOPc film clearly influences the device performance. Thus, the HMDS treatment provides a very attractive approach for attaining long-term air stability and a low V th shift for the VOPc based OFET devices.